Prosecutors' role and their relationship with the police in South Korea: In a comparative perspective - Choe, Dae-Hyun (International journal of law, crime and justice, 2018)
This study aims to explore prosecutors' role and their relationship with the police in South Korea. For the comparative study, six systems of criminal justice - England and Wales, the USA, France, Germany, Japan, and South Korea - were selected. The role of public prosecutors and their relationship with the police were effectively explored through a mixture of contrasting models: ‘coordinate & adjudicative' (1), ‘coordinate & investigative' (2), ‘hierarchical & adjudicative' (3), and ‘hierarchical & investigative' (4). The prosecutors in the model 1 emphasizes adjudicative role, and work together with the police in a coordinated fashion. In the model 2, the prosecutors can become actively involved in the investigation even where there is a coordinate relationship. The systems in the model 3, unlike the common law tradition, are based on a hierarchical structure. Nevertheless, the prosecutors do not become over-involved in the investigation due to some systemic limitations. The South Korean system is a typical example of the model 4 in which the investigation and prosecution are conducted by prosecutors. This may increase efficiency as it builds a factory conveyer belt without significant obstacles. However, considering the due process, such prosecutorial involvement in the investigation can cause some problems.